2021
DOI: 10.1007/s00429-021-02405-6
|View full text |Cite
|
Sign up to set email alerts
|

Convergence of forepaw somatosensory and motor cortical projections in the striatum, claustrum, thalamus, and pontine nuclei of cats

Abstract: The basal ganglia and pontocerebellar systems regulate somesthetic-guided motor behaviors, and receive prominent inputs from sensorimotor cortex. Additionally, the claustrum and thalamus are forebrain subcortical structures that have connections with somatosensory and motor cortices. Our previous studies in rats have shown that primary and secondary somatosensory cortex (S1 and S2) send overlapping projections to the neostriatum and pontine nuclei, whereas overlap of primary motor cortex (M1) and S1 was much w… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 115 publications
(149 reference statements)
0
7
0
Order By: Relevance
“…73,74,77 For example, M1 and S1 are heavily interconnected via reciprocal L2/3 and L5 connections, 78,79,80 and their projections overlap within dorsal striatum and even onto the same neuron. 73,81,82,83,84,85,86 While some studies treat striatal inputs as a uniform entity, 87,88 they have been shown to differ anatomically, 73,74,76 functionally, 89,90 and behaviorally. 89,91,92 Thus, the specific cortical and thalamic origin of striatal inputs likely has significance for understanding how the striatal circuitry integrates sensorimotor information to modulate behavior.…”
Section: Introductionmentioning
confidence: 99%
“…73,74,77 For example, M1 and S1 are heavily interconnected via reciprocal L2/3 and L5 connections, 78,79,80 and their projections overlap within dorsal striatum and even onto the same neuron. 73,81,82,83,84,85,86 While some studies treat striatal inputs as a uniform entity, 87,88 they have been shown to differ anatomically, 73,74,76 functionally, 89,90 and behaviorally. 89,91,92 Thus, the specific cortical and thalamic origin of striatal inputs likely has significance for understanding how the striatal circuitry integrates sensorimotor information to modulate behavior.…”
Section: Introductionmentioning
confidence: 99%
“…Notably, the dorsolateral striatum (DLS) is a site of overlap between inputs from M1 and S1 and plays a critical role in sensorimotor integration (Hoffer & Alloway, 2001;Hunnicutt et al, 2016;Makino et al, 2016;Hooks et al, 2018;Smith et al, 2022), but how these inputs are integrated by different cell types in DLS is still unclear.…”
Section: Introductionmentioning
confidence: 99%
“…Generally, cortical projections from functionally related brain regions show higher density and significant overlap amongst their projection fields in the striatum (Bolam et al, 2002; Hintiryan et al, 2016; Hunnicutt et al, 2016). Notably, the dorsolateral striatum (DLS) is a site of overlap between inputs from M1 and S1 and plays a critical role in sensorimotor integration (Hoffer & Alloway, 2001; Hunnicutt et al, 2016; Makino et al, 2016; Hooks et al, 2018; Smith et al, 2022), but how these inputs are integrated by different cell types in DLS is still unclear.…”
Section: Introductionmentioning
confidence: 99%
“…Generally, cortical projections from functionally related brain regions show higher density and significant overlap amongst their projection fields in the striatum ( Bolam et al, 2002 ; Hintiryan et al, 2016 ; Hunnicutt et al, 2016 ). Notably, the dorsolateral striatum (DLS) is a site of overlap between inputs from M1 and S1 and plays a critical role in sensorimotor integration ( Hoffer and Alloway, 2001 ; Hunnicutt et al, 2016 ; Makino et al, 2016 ; Hooks et al, 2018 ; Smith et al, 2022 ), but how these inputs are integrated by different cell types in DLS is still unclear.…”
Section: Introductionmentioning
confidence: 99%